That looks like ((X+3)*(X-2))^1/3 = 0
You should be able to get it from there.
2006-12-01 07:11:08
·
answer #1
·
answered by Jessica K 2
·
0⤊
1⤋
x=3
2006-12-01 07:11:20
·
answer #2
·
answered by Jordan E 1
·
0⤊
1⤋
Let x^1/3=t
Equation becomes:
t^2+t-6=0
=> t= -3 or t= 2
t= -3 => x^1/3= -3 => x= -27
t=2 => x^1/3=2 => x= 8
2006-12-01 07:13:03
·
answer #3
·
answered by Vu 2
·
2⤊
0⤋
X^2/3 + x^1/3 - 6 = 0
(x^1/3+3)(x^1/3-2)=0
x^1/3=-3
x=-27
x^1/3=2
x=8
2006-12-01 07:37:01
·
answer #4
·
answered by yupchagee 7
·
0⤊
0⤋
x^(2/3) + x^(1/3) - 6 = 0
Let y = x^(1/3)
Therefore, y^2 + y - 6 = 0
Factorise : (y + 3)(y - 2) = 0
So, y = -3 or +2
If y = -3, then x^(1/3) = -3
Cube both sides to get : x = -27.
If y = +2, then x^(1/3) = +2.
Cube both sides to get : x = 8
The 2 solutions are x = -27 or x = 8.
2006-12-01 07:16:27
·
answer #5
·
answered by falzoon 7
·
0⤊
0⤋
The first thing you have to do is multiply by the lowest common denominator. In this case, it's 3. So we get
x^2 + x - 18 = 0
Now, we solve for x. This isn't a factorable equation, so we have to use the quadratic formula.
x = (-1 +/- sqrt(1 - 4(-18)))/2
x = (-1 +/- sqrt(73))/2
So our two values are
x = (-1 + sqrt(73))/2 and
x=(-1 - sqrt(73))/2
2006-12-01 07:13:45
·
answer #6
·
answered by Puggy 7
·
0⤊
1⤋
X(2/3) +X(1/3)-6=0
2X/3+X/3=6
2X+X=6(3)
3X=18
X=6
Answer:6
2006-12-01 07:13:48
·
answer #7
·
answered by Anonymous
·
0⤊
1⤋
x^1/3 + 3)(x^1/3 - 2) = 0
x^1/3 = -3, 2
x = -27, 8
2006-12-01 07:12:39
·
answer #8
·
answered by Helmut 7
·
0⤊
1⤋
Vu got it right
2006-12-01 07:16:18
·
answer #9
·
answered by T 5
·
0⤊
0⤋
turd
2006-12-01 07:14:06
·
answer #10
·
answered by Anonymous
·
0⤊
3⤋